PENGARUH KONSUMSI SERAT TERHADAP PROFIL LIPID DAN PENANDA INFLAMASI: TINJAUAN LITERATUR - Simanjuntak, David Bryan Natanael; Dian Isti Angraini,; Hesti Yuningrum,; Dwita Oktaria, (Nusantara Hasana Journal, 2026)
Cardiometabolic diseases are a leading cause of global morbidity and mortality, with dyslipidemia and chronic low-grade inflammation playing key pathophysiological roles. Dietary factors, particularly dietary fiber intake, represent modifiable risk factors. This literature review aimed to evaluate the effects of dietary fiber consumption on lipid profiles and inflammatory markers. A systematic literature search was conducted using PubMed and Scopus with keywords related to dietary fiber, lipid profile, and inflammation. Of 157 identified articles, 8 met the inclusion criteria and were included in the analysis. The findings indicate that dietary fiber intake, especially soluble fiber, is consistently associated with reductions in total cholesterol, low-density lipoprotein (LDL) cholesterol, and triglyceride levels, particularly among individuals with type 2 diabetes mellitus, hyperlipidemia, and metabolic syndrome. In contrast, the effect of fiber on increasing high-density lipoprotein (HDL) cholesterol remains limited and inconsistent. Regarding inflammation, fiber consumption shows a more consistent anti-inflammatory effect on C-reactive protein (CRP), whereas its impact on proinflammatory cytokines such as interleukin-6 and tumor necrosis factor-α is variable. These differences may be influenced by fiber type, dosage, intervention duration, and participant characteristics. Overall, dietary fiber may serve as a safe and promising adjunct nutritional strategy for the prevention and management of cardiometabolic diseases.